Analisa Pengaruh Penambahan Jaringan Baru Dari Gardu Induk Masaran Ke PT. Sinar Agung Selalu Sukses Terhadap Susut Daya - Putra, Dedy Eka, Umar,ST.MT (2016)
The development of the electrical system in Indonesia at this time in particular has to increased efficiency in the distribution of electrical energy. Electricity needs a serious problem for the PT. PLN (Persero), this is due to the increasing needs of electricity supply industry. One way to improve efficiency in order to reduce power losses on the electrical system, by creating a new feeders of different substantion. PT. Sinar Agung Selalu Sukses (SASS) is one of the growing industries that want to increase the power supply. PT. SASS is currently obtaining supply from the substation Palur with the electrical load by 3,46 MW and has applied to the PT. PLN (Persero) for additional electrical load of 6,9 MW. PT. PLN (Persero) plans to create a new network to meet the burden required by PT. SASS to draw power from the substation Masaran directly to the PT. SASS which previously came from Substation Palur. This planning has been carried out technical analysis using ETAP software 12.6 to determine the extent of the contribution of the new feeder in shrinkage and improve network reliability. The simulation results of new network development planning of Substation Masaran is the reduced shrinkage of the original power loss 306 KW active power and reactive power losses amounting 986 kVAr be 231 KW active power losses and reactive power losses amounting 786 kVAr on the electrical system feeder 17 Palur.